KURIKULUM DAN SISTEM PEMBELAJARAN PONDOK PESANTREN Al-MAHMUD TANJUNGSARI SUMEDANG - Dadang Komara; Deni Tata Kusuma; Tatang Muh Nasir; Ceceng Saepulmilah; Yuliani (LPPM Sekolah Tinggi Ilmu Tarbiyah Al Marhalah Al Ulya Bekasi, Indonesia, 2025)
This research identifies the curriculum applied to the Al-Mahmud Tanjungsari Sumedang Islamic Boarding School which is different from the modern Islamic boarding school at this time. The method used in this study with a qualitative approach, namely describing what each journal, newspaper, book and others found, is then described with full calculation and care. The researcher also always meets face-to-face and discusses with each other about the curriculum at the Al-Mahmud Tanjungsari Sumedang Islamic Boarding School. The results of this research aim to produce strong human beings from the side of religious knowledge and strong from the social side (akhlak karimah), so that the Al-Mahmud Tanjungsari Sumedang Islamic Boarding School is very helpful in advancing a country or certain group in facing the challenges of the times in terms of the spiritual arid of society which is caused by being far from religious values. This is an education taught by Islamic teachings so that the world and the hereafter are balanced.